1985
DOI: 10.1172/jci112054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat on postprandial substrate oxidation and on carbohydrate and fat balances.

Abstract: To study the effect of dietary fat on postprandial substrate utilization and nutrient balance, respiratory exchange was determined in seven young men for 1 h before and 9 h after the ingestion of one of three different breakfasts: i.e., bread, jam, and dried meat (482 kcal: 27% protein, 62% carbohydrate, and 11% fat); bread, jam, and dried meat plus 50 g of margarine containing long-chain triglycerides (LCT); or bread, jam, and dried meat plus 40 g medium-chain triglycerides (MCT) and 10 g LCI margarine (858 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
154
3
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(178 citation statements)
references
References 21 publications
17
154
3
4
Order By: Relevance
“…23 For these calculations, urinary nitrogen excretion was assumed to be 0.11 mg kg À1 min À1 throughout all trials, based on data from similar studies in the literature. 24,25 We consider this assumption to be justified as data from previous studies have demonstrated that exercise with similar energy expenditures to the exercise intervention used in the present study, either with or without an energy deficit, does not influence postprandial protein oxidation rates. 25,26,27 The total area under the 8.5 h variable vs time curves (AUC), calculated using the trapezium rule, and the incremental AUC, calculated as the increment in AUC over baseline concentrations, were used as summary measures of the postprandial responses.…”
Section: Estimation Of Daily Energy Requirementsmentioning
confidence: 87%
“…23 For these calculations, urinary nitrogen excretion was assumed to be 0.11 mg kg À1 min À1 throughout all trials, based on data from similar studies in the literature. 24,25 We consider this assumption to be justified as data from previous studies have demonstrated that exercise with similar energy expenditures to the exercise intervention used in the present study, either with or without an energy deficit, does not influence postprandial protein oxidation rates. 25,26,27 The total area under the 8.5 h variable vs time curves (AUC), calculated using the trapezium rule, and the incremental AUC, calculated as the increment in AUC over baseline concentrations, were used as summary measures of the postprandial responses.…”
Section: Estimation Of Daily Energy Requirementsmentioning
confidence: 87%
“…Firstly, high-fat diets have high energy density and secondly, although the exact mechanism is still debated, it has been suggested by some investigators that consumption of high-fat diets leads to hyperphagia (Lissner et al, 1987;Stubbs et al, 1995). A possible third factor could be that dietary fat is mainly stored and not oxidized in the post-prandial period (Flatt et al, 1985;Schutz et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This association is likely explained by macronutrient imbalance favoring an excess fat intake above fat oxidation. Indeed, there is some evidence that excess dietary fat does not promote its own oxidation (Flatt et al, 1985;Flatt, 1988;Bennett et al, 1992) as does excess intake of carbohydrates (Flatt, 1988). It has also been demonstrated that high fat diets give way to overconsumption because fat seems to have a lesser effect on satiety than do other macronutrients (Blundell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%